2003
DOI: 10.1093/jn/133.7.2331
|View full text |Cite
|
Sign up to set email alerts
|

Rats Rapidly Reject Diets Deficient in Essential Amino Acids

Abstract: Omnivores must obtain diets balanced with respect to amino acids to support growth and protein synthesis. The standard paradigm used to study behavioral responses to amino acid deficiency combines deficient diets with dietary novelty. The objective of this study was to examine the effects of amino acid deficiency on the first meal of rats without the confounding effects of novelty. We report on a series of five studies of feeding behavior in rats. Rats were fed low protein diets for 5-7 d and then exposed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 15 publications
3
61
0
1
Order By: Relevance
“…It has been shown that the rapid rejection of amino acid-decent diets corresponds to decreases in the level of the limiting indispensable amino acid in the anterior pyriform cortex of rats (3,28). The smaller depression in both food intake (see below) and weight gain values obtained in this study compared with those previously published can be explained by essentially three factors: 1) the age of the rats; 2) the protein selected to design the diet; and 3) the nutritional requirements for rat growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the rapid rejection of amino acid-decent diets corresponds to decreases in the level of the limiting indispensable amino acid in the anterior pyriform cortex of rats (3,28). The smaller depression in both food intake (see below) and weight gain values obtained in this study compared with those previously published can be explained by essentially three factors: 1) the age of the rats; 2) the protein selected to design the diet; and 3) the nutritional requirements for rat growth.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the response to amino acid deficiency takes 15 min to develop [if previously fed a low threonine (Thr) diet; Refs. 22,28], but few data exist to understand biochemical changes related to bioenergetics at longer periods and in organs other than brain.…”
mentioning
confidence: 99%
“…For the in vitro studies, the tissue was taken without further dietary changes. For the gene-chip experiments, animals were fed BAS for the week prior to the experiment and then given a fresh food cup with either BAS, threonine devoid (Dev) or an IAA complete diet (corrected, COR i.e., Control, Cont) for 2 hr prior to collection of the APC tissue; for details and rationale for use of these diets see Koehnle et al [3].…”
Section: Animalsmentioning
confidence: 99%
“…Omnivorous mammals and birds show rapid sensing of IAA deficient food during the first meal; they reject a deficient diet within 20 min [3]. This adaptive behavioral response is associated with activation of neurons both in vivo [4] and in vitro [5], found in the ventro-rostral area of the APC (APCvr) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst other factors playing a role for the choose are the nutritional content of the food and the taste of the food, and rats' capability to identify and avoid poison and to choose the more nutritional feed, combined with their tendency to investigate new food sources, which results in manifold and flexible feeding behaviour. Investigations concerning essential and/or dangerous contents using laboratory rats are based on these characteristics (Fromentin and Nicolaidis, 1996;Koehnle et al, 2003), which has proven efficient (Benett and Henderson, 1972). Some food preference tests with various bread, common beets, beet roots, carrots, apples, and wheat have shown that rats were able to discriminate between organic and conventional products (Plochberger, 1989;Plochberger and Velmirov, 1992;Mäder et al, 1993).…”
Section: Introductionmentioning
confidence: 99%